Formação de professores de matemática, ciências naturais e física no contexto do PIBID/CAPES : discussão sobre estatísticas - Jesus, Marília Alana Costa de (2022)
The objective of this research was to discuss the statistics of teacher education in mathematics, physics and natural sciences in the current context, characterized by a chronic shortage of teachers in basic education and a series of public policies that sought to impact the statistics of undergraduate courses. The problem of the lack of teachers began in the last century, when the expansion of basic education was accompanied by the growing discredit of the profession and the reduction of training requirements for teaching. Currently, public policies, such as the Institutional Scholarship Program for Initiation to Teaching by the Coordination for the Improvement of Higher Education Personnel (PIBID/CAPES), seek to change this reality. It is in this context that this dissertation sought to analyze part of the qualitative data collected by the Research Group on Science Teaching at UFS and also collected and analyzed new quantitative data to compare with the results obtained in the first analysis. The results of this research are in three articles, submitted or already published in scientific journals. The first surveyed statistics on the training of mathematics teachers and analyzed the results found in the speeches of teachers from higher education institutions participating in PIBID/CAPES. The other two articles raised and analyzed the statistics of teacher training in natural sciences and. The results showed that PIBID/CAPES left a gap in the sense of honoring the teaching profession and show that current policies have made large investments in higher education, without changing the salaries of teachers in schools or their working conditions. It was also observed that the expansion of vacancies in higher education was a success. However, this achievement was the private initiative, which grew through public money. In addition, this expansion did not fully affect teacher training, as the Licentiate Degree in Natural Sciences is in the process of extinction. The candidate/vacancy ratio greater than 1.0 suggests that the idleness of vacancies is not due to the lack of candidates, but to their poor training or lack of interest by those approved in enrolling in the courses. There was also an increase in dropout rates, indicating that the scope and characteristics of public policies minimize their impact on these rates by limiting the number of students covered. Finally, it was noticed that the number of graduates over two decades was below what was necessary to make up for the lack of teachers, showing that the investments made by the federal government were not sufficient tachieve the objectives of the implemented public policies. Thus, it was concluded that although these policies are necessary, they are still insufficient, as they are unaccompanied by concrete actions in basic education classrooms that can improve the working conditions of teachers, which are the promoters of the shortage of professionals in schools.